Prevalence Of Childhood Obesity Among School Going Children and Its Associated Socio-Demographic Factors in Shirur Village, Bagalkot - Pavan S Kalasker; Arshiya Tarannum (National Journal of Community Medicine, 2016)
Introduction: The rise non-communicable diseases in India is not restricted to urban localities but fast spreading to rural areas.